2014
DOI: 10.2310/7290.2014.00032
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity in [18F]Fluorodeoxyglucose Positron Emission Tomography/Computed Tomography of Non–Small Cell Lung Carcinoma and Its Relationship to Metabolic Parameters and Pathologic Staging

Abstract: To investigate the relationships between tumor heterogeneity, assessed by texture analysis of [18F]fluorodeoxyglucose-positron emission tomography (FDG-PET) images, metabolic parameters, and pathologic staging in patients with non-small cell lung carcinoma (NSCLC). A retrospective analysis of 38 patients with histologically confirmed NSCLC who underwent staging FDG-PET/computed tomography was performed. Tumor images were segmented using a standardized uptake value (SUV) cutoff of 2.5. Five textural features, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 47 publications
2
32
0
2
Order By: Relevance
“…This is in line with previous studies showing that, for example, coarseness contains valuable information about survival for NSCLC patients or response to therapy for esophageal cancer patients . While sum and difference entropy (GLCM) showed to have prognostic value for NSCLC tumors …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This is in line with previous studies showing that, for example, coarseness contains valuable information about survival for NSCLC patients or response to therapy for esophageal cancer patients . While sum and difference entropy (GLCM) showed to have prognostic value for NSCLC tumors …”
Section: Discussionsupporting
confidence: 91%
“…36,37 While sum and difference entropy (GLCM) showed to have prognostic value for NSCLC tumors. [38][39][40] A drawback of our study is that only phantom data were included, although we attempted to make the study as clinically relevant as possible by using 3D printed phantom inserts reflecting heterogeneous tumor uptake pattern. It should be noted that our study was designed to explore the technical performance of radiomic features under controlled experimental conditions, thereby avoiding biological uncertainties or variations in imaging procedures.…”
Section: C Repeatable Featuresmentioning
confidence: 99%
“…Similar results have been previously reported wherein [18F]fluorodeoxyglucose-positron emission tomography-based texture features, including skewness, entropy, and contrast, correlated with the overall staging of nonsmall cell lung carcinoma and cervical cancer. 26,32 In our study, entropy and contrast showed a better correlation with overall staging as compared to that afforded by the traditional mean ADC value. This is consistent with a recent report by Vignati et al, in which the authors analyzed the correlation between ADC texture features and grading of prostate cancer.…”
Section: Discussionmentioning
confidence: 42%
“…; in which Range represents the number of discrete values (16,32,64,128), I represents the intensity of the original image, and H refers to the set of pixels within the delineated area. No statistically significant difference was found between the four range numbers (16,32,64,128), and the number of 32 was chosen in this study.…”
Section: Image Texture Analysismentioning
confidence: 99%
“…Recently, studies have suggested that the examination of spatial heterogeneity with computed tomography (CT) and the use of SUVs within solid tumors (particularly NSCLC) may provide prognostic information (8)(9)(10)(11)(12). Although these studies have generated compelling early evidence that heterogeneous tumors may lead to inferior outcomes, they have lacked adjustment for known prognostic factors and the use of proper validation techniques.…”
Section: Nuclear Medicine: Stage III Non-small Cell Lung Cancermentioning
confidence: 99%